SKINOMICS: Transcriptional Profiling in Dermatology and Skin Biology - Blumenberg, Miroslav (Bentham Science Publishers, 2012)
Recent years witnessed the birth of bioinformatics technologies, which greatly advanced biological research. These ‘omics’ technologies address comprehensively the entire genome, transcriptome, proteome, microbiome etc. A large impetus in development of bioinformatics was the introduction of DNA microarrays for transcriptional profiling. Because of its accessibility, skin was among the first organs analyzed using DNA microarrays, and dermatology among the first medical disciplines to embrace the approach. Here, DNA microarray methodologies and their application in dermatology and skin biology are reviewed. The most studied disease has been, unsurprisingly, melanoma; markers of melanoma progression, metastatic potential and even melanoma markers in blood have been detected. The basal and squamous cell carcinomas have also been intensely studied. Psoriasis has been comprehensively explored using DNA microarrays, transcriptional changes correlated with genomic markers and several signaling pathways important in psoriasis have been identified. Atopic dermatitis, wound healing, keloids etc. have been analyzed using microarrays. Noninvasive skin sampling for microarray studies has been developed. Simultaneously, epidermal keratinocytes have been the subject of many skin biology studies because they respond to a rich variety of inflammatory and immunomodulating cytokines, hormones, vitamins, UV light, toxins and physical injury. The transcriptional changes occurring during epidermal differentiation and cornification have been identified and characterized. Recent studies identified the genes specifically expressed in human epidermal stem cells. As dermatology advances toward personalized medicine, microarrays and related ‘omics’ techniques will be directly applicable to the personalized dermatology practice of the future.